Mortality, cardiovascular risk, and androgen deprivation therapy for prostate cancer: A systematic review with direct and network meta-analyses of randomized controlled trials and observational studies. Issue 24 (June 2016) - Scailteux, Lucie-Marie; Naudet, Florian; Alimi, Quentin; Vincendeau, Sébastien; Oger, Emmanuel
Abstract : Abstract: Androgen deprivation therapy (ADT) is a cornerstone therapy for advanced prostate cancer (PCa). We hypothesized that cardiovascular (CV) risk is different across the various ADT modalities to compare their effects on CV morbidity and mortality, and all-cause mortality in patients with PCa. To investigate more in depth potential CV risk heterogeneity focusing on coronary (main outcome) and cerebrovascular risk, CV, and overall mortality. We performed a Medline and Embase query, without language restriction, since 1950 up to July 2014. We included randomized controlled trials (RCTs) and observational studies providing that they compared at least 1 ADT modality to another one or to placebo and they gave data on CV event or all-cause mortality. Sixty-eight studies out of 3419 met our eligibility criteria. Eleven observational studies were analyzed. Direct meta-analyses showed that antiandrogen was associated with a 30% decrease risk for myocardial infarction (MI) compared to GnRH agonists (RR, 0.70 [0.54–0.91]); combined androgen blockade (CAB) was associated with a 10% increase risk for stroke when compared to antiandrogen (RR, 1.10 [1.02–1.19]). With regard to RCTs, 57 were included: direct meta-analyses suggested that CAB was associated with a 10% decrease of all-cause mortality when compared to GnRH agonist (RR, 0.90 [0.82–1.00]). Network analysis could only be performed for all-cause mortality and it remains difficult to disentangle benefit (positive impact on cancer survival) and risk (including CV risk). The impact of the ADT modalities on CV morbidity remains difficult to quantify and more detailed prospective collection is required. Registration: PROSPERO, CRD42014010598. Abstract : Supplemental Digital Content is available in the text